Static and dynamic cardiac modelling: initial strides and results towards a quantitatively accurate mechanical heart model - Aristokleous, Nicolas; Constantinides, Christakis; Perperides, D. (My University, 2010)
Magnetic Resonance Imaging (MRI) has exhibited significant potential for quantifying cardiac function and dysfunction in the mouse. Recent advances in highresolution cardiac MR imaging techniques have contributed to the development of acquisition approaches that allow fast and accurate description of anatomic structures, and accurate surface and finite element (FE) mesh model constructions for study of global mechanical function in normal and transgenic mice. This study presents work in progress for construction of quantitatively accurate threedimensional (3D) and 4D dynamic surface and FE models of murine left ventricular (LV) muscle in C57BL/6J (n=10) mice. Constructed models are subsequently imported into commercial software packages for the solution of the constitutive equations that characterize mechanical function, including computation of the stress and strain fields. They are further used with solid-free form fabrication processes to construct model-based material renditions of the human and mouse hearts.
Keywords: Cardiovascular system; Image processing; Magnetic resonance imaging; Rapid prototyping